‘If you don’t swim with us you are a pig’: experiences of children with albinism living in a rural area in Zimbabwe - Mutambara, Julia; Mudhovozi, Pilot; Madanhire, Charles (Dzimbabwe Journal of Multidisciplinary Research, 2019)
The research explored the problems that children with albinism face in adapting to rural life as well as their experiences of and reaction to stigma. The participants of the study were 7 students living with albinism drawn from three schools in Gutu District of Masvingo Province in Zimbabwe. In-depth interviews were conducted with these 7 students and thematic analysis was used to analyse the responses. The study established that rural life poses a challenge for children with albinism in that they could not participate in activities that are done by other children like herding cattle, fetching firewood, swimming in the river and cooking using open fire. This leads to their isolation. The participants revealed that they were subjected to various forms of stigma and discrimination. 1n reaction to stigma, children reported that they sometimes cry, became angry and prayed to God. The research recommends increased education, advocacy and protection of the rights of pupils living with albinism so as to combat stigma, discrimination, mocking and isolation.